أثر التطور المالي على النمو الاقتصادي في الجزائر خلال الفترة 1970-2019 - خوري, نبيل (جامعة الوادي - University of Eloued, 2022)
يهدف البحث الى دراسة أثر التطور المالي على النمو الاقتصادي في الجزائر للفترة 1970-2019 باستخدام نماذج أشعة الانحدار الذاتي. توصلت النتائج الى ما يلي: يشير اختبار السببية الى وجود علاقة ذات اتجاهين بين المتغيرتين، كما تبين دوال الاستجابة وجود أثر سلبي للتطور المالي على النمو الاقتصادي في المدى الطويل، بينما يوضح تفكيك التباين أن نسبة مساهمة صدمة التطور المالي في تفسير تغيرات النمو الاقتصادي تساوي 18.92% في السنة العاشرة التي تلي حدوث الصدمة. يمتاز القطاع المالي الجزائري بهيمنة البنوك العمومية التي يقع على عاتقها وظيفة تمويل المؤسسات. كما يعتبر حجم القطاع المالي ضعيف نسبيا مما يعيق وظيفته التمويلية. كما يشهد الاقتصاد الجزائري نقص في كفاءة الوساطة المالية نظرا للنسبة المتدنية للقروض البنكية الداخلية الممنوحة للاقتصاد. The paperaims to study the impact of financialdevelopment on economicgrowth in Algeria(1970- 2019).The methodology is based on the VAR modelling.The researchstudy gives the following results: (i) the causality test indicates that there is a bidirectional relationship between the two variables;(ii) the response functionsshow a long-term negative impact of financial development on economic growth;(iii) The variance decomposition shows that a shock in the financial development variable contributes to explain 18.92% of the economic growth variance in the tenth year.The financial sector in Algeria is dominated by the state-owned banks; the size of the financial sector is relatively small, this situation limits banks to fully playing their role in financing companies. Finally, a lack of financial intermediationis observed for the Algerian economy,mainly due to the low percentage of internal bank loans granted to the economy
Impact of financial development on economic growth in Algeria over the period 1970-2019
مقال